Penerapan metode ARIMA terhadap perkiraan harga saham pada perusahaan Bank Syariah Indonesia (BSI) - Auliah, Umi; Rafidah, Rafidah; Mubarak, Fadhlul (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study uses a quantitative research method that aims to apply time series graphics to Indonesian Sharia Banks. The right guess is the main information needed by investors in determining the next investment strategy, one of which is ARIMA (Autoregressive Integrated Moving Average). This method is a method that uses the present value and past value of the dependent variable to produce accurate short-term forecastes.This study aims to determine the stock prediction model for Bank Syariah Indonesia (BSI) companies using the Autoregressive Integrated Moving Average (ARIMA) method and to determine the results of this method. The arima method is used to solve seasonal time series. Data on total daily share prices of Bank Syariah Indonesia (BSI) for the 2020-2022 period totaling 1,095 days obtained from https//yahoo.finance and Bank Syariah Indonesia's annual financial reports.This type of research method is descriptive quantitative data source is secondary data. With the help of the R program syntax with the Best ARIMA forecasting model (0,0,0) with the results of research on stock price data for the 2023 period, it has increased compared to the 2020-2022 period.